Youth Education Efforts of the 1940s: Representative Activities of the Mass-dance Cult-programme and the Beginnings of the Academic Dance-research in Budapest - Ábrahám, Nóra (Ethnographica et Folkloristica Carpathica, 2024)
My paper aims to present the dance culture of the 1940’s and explore its scientific approach to dance. According to results of my research, the “national-rescue activity” originating in Budapest looked for the promise of demonstrating “cultural-superiority” in youth-education. Movement-artists and newly formed amateur ensembles also played role in this. The initial dance-research followed the European research direction, considered the application of ethnological theories as the basis. When examining the interaction of city and countryside with a cultural-historical anthropological approach, my questions formulated in my writing: Did the village research and Scientific Institute-work in the 1940’s have an impact on the style of dance that also played a representative role, appearing as a result of the youth education efforts in Budapest? How does appear in the source-works that published the research-results of that time? My paper seeks the answers to these questions.